PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF ONLINE MENGGUNAKAN KelasKita BERBANTUAN SOFTWARE GEOGEBRA PADA MATERI PERSAMAAN KUADRAT - Fatoni, Muhamad Faizal; Dafik, Dafik; Fatahillah, Arif (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research aims to develop an online interactive learning media use assisted KelasKita software Geogebra on quadratic equations. Learning media developed is KelasKita-assisted software Geogebra. This research trial underway in SMP 7 Jember on grade VIII h. This is the kind of research the research development. This research using model Thiagarajan consisting of 4 stages are: 1) the stage of definition 2) stage design of 3) development stage 4) deployment phase. The results of the development on the research of the kevalidan of the analysis of test validation sheets from 3 correlation coefficients obtained validator the validator I of 0.97 0.94 registration validator II, and III of 0.91 validator from the validators valid category earned third with very high interpretation, test the practicality of the analysis of the percentage of the question form students obtained the percentage of 95% by category, and test the effectiveness of the analysis of the value of the test results of the study with a percentage of 94.7% of 38 students scored above the KKM with effective results. Based on the results of these learning media development shows that online interactive learning media use Geogebra software assisted KelasKita meets validity, practicality, effectiveness so that it is said to be worthy of use in learning. Interactive results between teachers and students in KelasKita shows the percentage of students who follow 47.36% for the method graph quadratic equations, and 42.1% to complete the perfect squares method of 38 students. Keywords : Development, Media, KelasKita, Geogebra, Quadratic Equation